A Bayesian perspective on single-shot laser characterization - J. Esslinger; N. Weiße; C. Eberle; J. Schröder; S. Howard; P. Norreys; S. Karsch; A. Döpp (Proceedings of the National Academy of Sciences, 2025)
We introduce a Bayesian framework for measuring spatiotemporal couplings in ultraintense lasers that reconceptualizes what constitutes a “single-shot” measurement. Moving beyond traditional distinctions between single- and multishot devices, our approach provides rigorous criteria for determining when measurements can truly resolve individual laser shots rather than statistical averages. By contextualizing single measurements, this framework shows that single-shot capability is not an intrinsic device property but emerges from the relationship between measurement precision and predictability. Implementing this approach with a custom measurement device at the ATLAS-3000 petawatt laser, we provide quantitative uncertainty bounds on pulse front tilt and curvature. Notably, we observe that our Bayesian method reduces uncertainty by up to 60% compared to traditional approaches. Through this analysis, we reveal how the interplay between measurement precision and intrinsic system variability defines achievable resolution-insights that have direct implications for applications where precise control of laser–matter interaction is critical.